In vivo Analysis of Normal Optic Nerve in an Elderly Population Using Diffusion Magnetic Resonance Imaging Tractography - Moon, Yeji; Yang, Jin-Ju; Lee, Won June; Lee, Ji Young; Kim, Yu Jeong; Lim, Han Woong; , The Alzheimer's Disease Neuroimaging Initiative (ADNI); Weiner, Michael W; Aisen, Paul; Petersen, Ronald; Jack, Clifford; Bernstein, Matthew; et al. (Frontiers in Neurology, 2021)
Purpose: To quantitatively investigate the microstructural properties of the optic nerve (ON) in vivo using diffusion magnetic resonance imaging (dMRI) tractography in an elderly population and to determine the differences between the ON diffusion properties stratified by basic demographics Methods: We measured fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD) and axial diffusitivty (AD) of the intraorbital ON in cognitively normal controls selected from the Alzheimer’s Disease Neuroimaging Initiative 3 database (n =104, mean age 73.8 ± 8.1 years) using dMRI probabilistic tractography and evaluated the correlation between diffusion parameters and demographic factors. Diffusion parameters were measured in 20 equidistant nodes along the tract, and the data from proximal 70% (14 nodes) of the intraorbital ON were averaged Results: The mean FA of the intraorbital ON was 0.392 ± 0.063 and the mean MD was 1.163 ± 0.165 μm2/s. The mean RD was 0.882 ± 0.152 μm2/s, and the mean AD was 1.693 ± 0.183 μm2/s. The multiple linear regression model showed a negative correlation between FA and age. FA in females was significantly higher than males, whereas RD in female were significantly lower. Conclusions: We measured the diffusion properties of the intraorbital ON using dMRI tractography in an elderly cognitively normal population. The diffusion properties detected by dMRI tractography may substantially reflect the microstructure of the ON.